Brecht’s Life of Galileo: Staging a theory of the encounter of practices - Alejo Stark (Galilæana)
Brecht’s Life of Galileo provides elements for elaborating what I call “a theory of the encounter of practices”. The concept of the encounter pushes back against teleological theories that predestine modern science to operate as an instrument of domination. I argue that Life of Galileo stages the missed encounters in modernity between science, politics, and art at the same time as it foregrounds the emancipatory power of science. I trace the encounter of practices from the play’s opening scenes – highlighting what I call Galileo’s “double life”. Then, I turn to the most important scene of the play, Scene 10, in which political and artistic practices repurpose Galileo’s novel inventions for their emancipatory desires. In the virtual potentialities of this encounter, that is, despite the missed encounter between Galileo and “the people”, Brecht’s Life of Galileo continues to be fruitful for theorizing the emancipatory power of science.